3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28
3a + 2b = c (find a in terms of b and c)3a +2b -2b = c - 2b3a = c - 2b3a/3 = (c - 2b)/3a = (c - 2b)/3In order to find the value of a, you can give any values to b, and c (except a zero value).
If a plus b equals 6 what is the value of 3a plus 3b
It is an expression that can be simplified to: 3a-2b+c
3a + 2b = 4If b = 7, then3a + 2(7) = 43a + 14 = 4Subtract 14 from each side:3a = -10Divide each side by 3:a = -10/3
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)
It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus
Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).